2019
DOI: 10.3390/ijms20030791
|View full text |Cite
|
Sign up to set email alerts
|

Response of Tibetan Wild Barley Genotypes to Drought Stress and Identification of Quantitative Trait Loci by Genome-Wide Association Analysis

Abstract: Tibetan wild barley has been identified to show large genetic variation and stress tolerance. A genome-wide association (GWA) analysis was performed to detect quantitative trait loci (QTLs) for drought tolerance using 777 Diversity Array Technology (DArT) markers and morphological and physiological traits of 166 Tibetan wild barley accessions in both hydroponic and pot experiments. Large genotypic variation for these traits was found; and population structure and kinship analysis identified three subpopulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 71 publications
0
12
0
Order By: Relevance
“…To the best of our knowledge, few genetic studies have investigated the complex agronomic traits in Tibetan qingke barley (Zhang et al, 2019 ). Previous reports have included only a limited number of qingke barley accessions to identify potential signals of adaptation and domestication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, few genetic studies have investigated the complex agronomic traits in Tibetan qingke barley (Zhang et al, 2019 ). Previous reports have included only a limited number of qingke barley accessions to identify potential signals of adaptation and domestication.…”
Section: Discussionmentioning
confidence: 99%
“…With the emergence of more cost-effective, high-throughput genotyping technologies, single nucleotide polymorphisms (SNPs) related to HD have been identified by genome-wide association studies (GWAS) (Pasam et al, 2012 ; Visioni et al, 2013 ; Genievskaya et al, 2018 ), PH (Alqudah et al, 2016 ; Almerekova et al, 2019 ), leaf area (Alqudah et al, 2018 ), spike architecture (Comadran et al, 2011 ) and grain yield (Ingvordsen et al, 2015 ; Xu et al, 2018 ) in barley. However, the genetic study of complex agronomic traits in qingke barley is limited (Zhang et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…With the genetic linkage maps developed on the SSR markers, 17 QTLs associated with grain width, grain length, and 1000-grain weight were identified in oat [ 47 ], and two main-effect QTLs related to plant height were observed in foxtail millet [ 48 ]. Genome-wide association studies (GWAS) have been used to identify the association between SSR markers with the nudity of oat grain [ 49 ] as well as with the photoperiod sensitivity of foxtail millet cultivars [ 50 ] and the relationships between DArT markers and the response of Tibetan wild barley genotypes to drought stress [ 51 ]. In recent years, whole genome sequencing has been used to mine useful genes in UGCs.…”
Section: Germplasm Resourcesmentioning
confidence: 99%
“…Thus, by performing a GWAS analysis of 166 Tibetan wild barley accessions varying for their drought response, Zhang et al. (2019) identified QTL markers associated with tolerance. When searching for genes co‐localizing with these QTL, these authors found several H + K + ‐ATPases, which enable the transport of osmolytes such as organic acids, and also of K + between apoplast and cytoplasm.…”
Section: Functional Genomics As a Tool To Explore Drought‐induced Protective Mechanisms In Barleymentioning
confidence: 99%
“…When performing GWAS analysis of 166 Tibetan wild barley accessions, Zhang et al. (2019) determined QTL associated with peroxidase and catalase activity under drought stress, and identified six genes encoding peroxidases close to the markers associated with better tolerance. H 2 O 2 scavenging appears as a key process conferring drought tolerance since two genes coding for catalases were identified as candidates in QTL associated with tolerance traits at germination and seedling stages when testing 60 Egyptian contrasted genotypes (Moursi et al., 2020).…”
Section: Functional Genomics As a Tool To Explore Drought‐induced Protective Mechanisms In Barleymentioning
confidence: 99%